ShK‐modified UCMSCs Inhibit M1‐Like Macrophage Polarization and Alleviate Osteoarthritis Progression via PI3K/Akt Axis - Wenshu Wu; Xueying An; Wang Gong; Lin Yang; Na Liu; Bin Liu; Baosheng Guo; Qing Jiang; Lan Li (Advanced Science)
Abstract The potassium channel Kv1.3 plays an important role in regulating immune cell functions in many inflammatory diseases whereas rarely in osteoarthritis (OA). Here, it is demonstrated that the Kv1.3 of macrophages is upregulated in response to LPS stimulation, as well as in human OA synovium samples than non‐OA. Administration of Stichodactyla toxin (ShK), a Kv1.3 blocker, significantly inhibited cartilage degeneration and synovial inflammation in animal models of OA in vivo by inhibiting M1 macrophage polarization and reducing the production of inflammatory factors. In this study, a transgenically engineered human umbilical cord mesenchymal stem cell (UCMSC) delivery system is developed that secreted a peptide ShK, a Kv1.3 potassium blocker, into the knee articular cavity. Collectively, the results identified Kv1.3 as a potential therapeutic target for OA and demonstrated the efficacy of using ShK transgenic engineered UCMSCs as a delivery for the peptide in OA treatment.